DZIENNIKARSTWO W XXI WIEKU – MIĘDZY POTRZEBAMI SPOŁECZNYMI A WYMOGAMI RYNKU - Nierenberg, Bogusław (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article aims to present the condition of the journalist profession at present and in the past. The article puts forth two research theses: 1. At present, as a result of new technologies being applied in the new media, the traditionally understood correspondent journalists are being supplanted by media workers - employees of media organizations and 2. new forms of electronic transmission do not rule out the mission, traditionally connected with the performance of the journalism profession. Both of the theses were proven by means of case studies connected to the figures of Ryszard Kapuściński, Polish journalist and publicist, and American blogger Matthew Lee. Moreover, technological processes which impact the process of shaping of the journalist profession was performed.